Zimbabwe's political, social, and economic prospects: 2019 in review - Mafa, Kwanisai Mafa (Hampton Institute, 2020)
After the 2018 harmonized elections which gave the ZANU PF party the mandate to rule, President Emmerson Mnangagwa appealed to all political party Presidents who contested in the elections to come together in a national dialogue and find a way to stop the toxic political polarization which continues to divide the Zimbabwean nation. Another reason for the national dialogue was to provide a viable platform for contributing towards lasting solutions to the challenges that confront the country. All the 19 political parties accepted the President’s invitation to Political Actors Dialogue (POLAD) and the main opposition Movement for Democratic Change (MDC) refused on the basis that they don’t recognize the Presidency of Emmerson Mnangagwa.